Malawi : Technical Assistance Report-Strengthening Fundamental Controls and Reporting. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses the technical advice and recommendations of the IMF mission to the authorities of Malawi regarding strengthening fundamental controls and reporting. The government is determined to restore control over public funds. Considerable progress has been made on the reconciliation of the 2015/16 transactions of selected bank accounts. Issues related to transactions before 2015/16 should be investigated and resolved. The auditor general and the Central Internal Audit Unit (CIAU) are investigating unmatched or potentially duplicate payments for 2009-June 2015. It is recommended that the accountant general investigate possible duplicate payments identified by the CIAU.